Postcolonial Biotech: Taiwanese Conundrums and Subimperial Desires. Issue 4 (1st December 2017) - Liu, Jennifer A.
Abstract : Where most accounts of biotech in Taiwan—indeed, globally—focus on its economic potential and its potential to heal various ills, a postcolonial and subimperial framing insists on attention to often underexamined aspects, for example, how biotech practices reflect specific nationalist desires and rely on forms of exploitation. A postcolonial and subimperial framing insists on the inclusion of other stories. Drawing Taiwan's nanxiang (southward) policies and Indigenous rights into a biotech frame, I suggest that such policies and desires create potential contradictions that are not easily resolved. For example, hard-won policies preventing the collection of Indigenous genetic samples may foreclose studies that might address pronounced health disparities. And the scope of a national biobank project aimed toward a global Chinese ethnic community is limited by competing claims of Taiwanese genetic uniqueness. One possible resolution envisions Taiwan biotech as a site for imagining possible futures outside enduring colonial influences and subimperial desires.